Cardiac surgery in the adult (McGraw-Hill, Medical Pub. Division, 2003)
The definitive resource covering all aspects of heart surgery in adults! With over 1,100 step-by-step illustrations detailing each procedure, this comprehensive text provides guidance through all the operations and operative techniques of the discipline. This edition features renewed emphasis on minimally invasive procedures as well as a large amount of new illustrations depicting the surgical anatomy.